LAKON JAKA BLUWO KARYA BAMBANG SUWARNO DALAM PARADIGMA STRUKTURALISME LÃ‰VI-STRAUSS - Eko Prasetyo; S., Sarwanto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2016)
This research is based on the assumption that lakon Jaka Bluwo by Bambang Suwarno inwayang gedhog performance represents the Javanese knowledge sourced from mythology thatis universally received to interpret their world, both microcosm as well as macrocosm. For thereason, it needs to gain the messages contained in the wayanglakon. The material objectchosen in the research is lakon Jaka Bluwo that is one of Panji stories which is often presented inwayang gedhog and wayang topeng performance. The research aims to convey the messagescontained in lakon Jaka Bluwo using the paradigm of Levi - Strauss structuralism. The result ofresearch shows that the structuralism analysis produces a new meaning out of the meaning inlakon Jaka Bluwo. The meaning is a deep structure which is different from the performance aswell as dramatic structures which are empirically understood. Lakon Jaka Bluwo is guessed to bea Javanese way to describe the various knowledges about the balanced principles of human livesthat is one who is able to do the inner and outer dutiesequally.Keywords: Lakon Jaka Bluwo, Bambang Suwarnoâ€™s work, structuralism, Levi-Strauss.